Strategies for Screening and Managing Cancer in Family Practice in Saudi Arabia - Mohammed Ali Alhowaish, Jawaher Ali Alhowaish, Rawan Deham Aledeilah, Khulud Awad AlTarfawi, Anwar Matar Alsulobi, Anfal Marzouq Alanazi; Afaf Amer Alenazi‏, Ruqayyah Batel Shati Alanazi, Abdullah Ahmed Alfaifi, Abdulrahman Mansour Abdulrahman AlFawaz, Mohammed Waheeb Mohammed Alwhibi, Omar Abdulaziz Alzamel (Journal of International Crisis and Risk Communication Research, 2024)
In Saudi Arabia, family practitioners play a critical role in the screening and management of cancer, necessitating the implementation of comprehensive strategies tailored to the country's specific epidemiological trends and healthcare system. Effective screening programs should focus on high-incidence cancers, including breast, colorectal, and lung cancers, which have increasingly affected the Saudi population. Family physicians can utilize guidelines provided by national health authorities to conduct regular screenings, promote awareness, and educate patients about risk factors and early signs of cancer. Integrating community health initiatives can facilitate access to cancer screenings in rural and underserved areas, ensuring that early detection efforts reach all segments of the population. Managing cancer within a family practice setting involves a multidisciplinary approach, emphasizing collaboration between various healthcare professionals. Family physicians should be equipped with updated knowledge on treatment protocols and palliative care options, allowing them to provide empathetic support to patients undergoing cancer treatment. Additionally, fostering strong communication with oncologists and mental health specialists enables a more holistic management plan that addresses both medical and psychological needs. Continued professional development and training in cancer care for family practitioners will enhance their ability to deliver quality care, ultimately improving patient outcomes in Saudi Arabia.